The Effect of Adapting IFRS 15 on Auditing Procedures for Auditors in Iraqi Environment - Al- Mashhadani, Bushra N. Abdullah; Mohammad, Mohammad Ibrahim (Journal of Economics and Administrative Sciences, 2021)
The purpose of the International Financial Reporting Standard (IFRS 15) is to determine the basis for reporting useful information to the users of financial reports on the nature, amount, timing and uncertainty about revenues and cash flows arising from a contract with a customer. It is based on specific conditions for recognizing revenue from the contract. When the two parties to the contract or one of them fulfil the performance obligations, specifically after the customer has the ability to exercise control over the product or service that is the subject of the contract. As a result of the failure of the revenue reporting requirements in the Iraqi environment to provide adequate and honestly representative information on the outcome of the activity and the financial position as a result of the failure of the unified accounting system to provide an appropriate mechanism for measuring, recognizing and disclosing the revenue compared to the requirements of the International Financial Reporting Standard (IFRS 15), Consequently, the deficiency of audit program and guide issued by the Federal Office of Financial Supervision, which was limited to its procedures limited to a specific type of activity, as well as the absence of audit programs approved by local auditing firms and account auditors in private offices, so the matter requires indicating the importance of adopting the international financial reporting standard (IFRS 15) and the impact of this on the audit procedures that must be approved by auditors when auditing revenues, and the researchers based on the opinions of a sample of academics and professionals in this field by designing a questionnaire that focused on the importance of adopting the above standard and indicating the impact of the adoption on revenue audit procedures in the Iraqi environment. Based on two hypotheses:Hypothesis 1: There are significant differences in significance regarding the importance of adopting the International Financial Reporting Standard (IFRS 15).Hypothesis 2: There are significant differences in significance regarding the impact of adopting the IFRS 15 standard on revenue audit procedures in the Iraqi environment.      The research sample was represented by (academics) faculty members in Iraqi universities represented by professors in accounting departments in them, as well as account auditors (professionals) working in private auditing offices and companies, as well as account auditors working in the Federal Office of Financial Supervision, since they have the ability to read And understanding the guidance contained in the new international financial reporting standards, including the International Financial Reporting Standard (15) “Recognition of revenue from contracts with customers